Pelaksanaan Keterampilan Kehidupan Sehari-hari dalam Mencuci Pakaian Kelayan Gangguan Penglihatan Kelas Persiapan X di PSBN Tuah Sakato Padang - Lubis, Ridoan; Damri, Damri (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
Abstract The purpose of this research is to knowing and to describing preparation, implementation, and evaluation of study result of client with visual impairment in preparation class at PSBN Tuah Sakato Padang. This research is using descriptive methods with qualitative approach which is conducted in preparation class at PSBN Tuah Sakato Padang. The subject of the research is the instructor of daily life skill and client with visual impairment. The technique that used for collecting data is observation, interview, and documentation.The validity of data is tested with credibility tes of triangulation technique. The result of this research shows that preparation of daily living skill of client with visual impairment in washing clothesis done by preparing tools and materials and facilities and infrastructure that support these activities. To be implementation, the instructor uses the syllabus that is guide by KKS guidebook to determine the goals, matreials, methods, and media which is adjusted client with visual impairment skill and condition with individual approach. The result of evaluation was done after the learning procces. The tools of evaluation that used were non test and test, but in the assessment, the instructor used non-test by sawing the washing result of the client with visual impairment. Non-test evaluation was used due to limitted time. The assessment was done in learning procces or out of learning procces.